A methylation platform of unconventional inert aryl electrophiles: trimethylboroxine as a universal methylating reagent. Issue 23 (2nd June 2020) - Feng, Boya; Yang, Yudong; You, Jingsong
Abstract : A universal platform for catalytic methylation of a series of unconventional inert aryl electrophiles with trimethylboroxine (TMB) is established, which provides a synthetic chemist's toolbox for the construction of methylated arenes. Abstract : Methylation is one of the most fundamental conversions in medicinal and material chemistry. Extension of substrate types from aromatic halides to other unconventional aromatic electrophiles is a highly important yet challenging task in catalytic methylation. Disclosed herein is a series of transition metal-catalyzed methylations of unconventional inert aryl electrophiles using trimethylboroxine (TMB) as the methylating reagent. This transformation features a broad substrate type, including nitroarenes, benzoic amides, benzoic esters, aryl cyanides, phenol ethers, aryl pivalates and aryl fluorides. Another important merit of this work is that these widespread "inert" functionalities are capable of serving as directing or activating groups for selective functionalization of aromatic rings before methylation, which greatly expands the connotation of methylation chemistry.